HUBUNGAN STATUS GIZI PRAKONSEPSI TERHADAP PENGETAHUAN DAN SIKAP WANITA USIA SUBUR DI KP. KOBAK BAYA RT 001/006 DESA SUKAMANAH KECAMATAN SUKATANI KABUPATEN BEKASI TAHUN 2022 - Masluroh, Masluroh; Suherlan, Larasati Audy Rachma (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
Background: In general, nutritional problems in Indonesia are still dominated by malnutrition. The problem of undernutrition in the female group affects nutritional status in the next life cycle period (intergenerational impact). The preconception period is one of the most important in terms of nutritional status. The nutritional and health status of WUS during preconception has received little attention, with one exception being preconceptional women suffering from malnutrition, such as Chronic Energy Deficiency (KEK). The preliminary survey data from Kp. Kobak Baya Rt 001/006 Sukamanah Village, Sukatani District, Bekasi Regency revealed that in Rt 001/006, out of 10 WUS samples, 1 WUS (10%) had good preconception nutrition knowledge, 2 WUS (20%) had sufficient knowledge, and 7 WUS (70%) had insufficient knowledge. Research Objectives: To determine the relationship between preconceptional nutritional status and knowledge and attitudes of women of childbearing age in Kp. Kobak Baya RT 001/006 Sukamanah Village, Sukatani District, Bekasi Regency in 2022. Research Method: Analytic with cross sectional, the sample in this study were women of childbearing age in Kp. Kobak Baya Rt 001/006 as many as 147 people, and the sampling technique used was purposive sampling with a chi-square test. there is a significant relationship between preconceptional nutritional status and women of childbearing age's knowledge and attitudes in Kp. Kobak Baya Rt. 001/006 Sukamanah Village, Sukatani District, Bekasi Regency in 2022. Conclusion: There is a significant relationship between preconception nutritional status and the knowledge and attitudes of women of childbearing age in Kp. Kobak Baya Rt 001/006 Sukamanah Village, Sukatani District, Bekasi Regency in 2022, with chi-square results of p = 0.000. And the attitude variable has a greater risk of preconception nutritional status with a value (OR = 4.526) compared to knowledge (0.314).Keyword : Nutritional Status, knowledge, attitude